IDENTIFIKASI DAN ANALISIS KANDUNGAN MAKRONUTRIEN GLUKOMANAN UMBI PORANG (Amorphophallus onchophyllus) - Bekti Nugraheni; Anastasia Setyopuspito P; Yustisia Dian Advistasari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTThe purpose of this study is identification and analysis of the macronutrient glucomannan from porang tuber (Amorphophallus onchopyllus). The stages done in this research are extraction, identification, and macronutrient analysis of glucomannan of the porang tuber. Prior to extraction, the oxalic acid was removed from porang tuber using mixture of 2% lime juice and 5% lime, then the glucomannans was extracted using ultrasonic method. The glucomannan then was identified using Fourier transform infra red spectrometer (FTIR) instrument and macronutrient analyzer such as Soxhlet method for fats and fibers, Kjedahl method for protein, and Antrone method for carbohydrates. The results of identification using FTIR showed the presence of β-pyranose at wave numbers of 900-810 cm -1 . The carbonyl on on acetyl group was found at 1726 cm-1 . The area between 870-800 cm-1 showed the β-glycosidic and β-manosidic compounds. The C-O ether group was shown in the area of 1260-1200 cm -1 , while for C-O alcohol was shown in the area of 1050 cm-1 showed the C-O bond in alcohol. At 2925 cm-1 it showed C-H, while at 3000-3700 cm-1 O-H group. The levels of porang glucomannan macronutrients included fat at 0.50%, protein at 1.05%, fiber at 22.34%, and carbohydrates at 31.33%.Key word: Porang tuber, glucomannan, FTIR, macronutrient analysis.